Casein whey as booster for anaerobic co-digestion of primary sludge : a thesis presented in partial fulfilment of the requirements for the degree of Master of Engineering in Environmental Engineering - Güttler, Johanna (Massey University, 2012)
Spare capacity found in many municipal primary sludge digesters could be used to improve the biogas production through the addition of other organic waste. This work investigates the potential of casein whey as an additional substrate. The amount of whey required for maximum biogas production and stable reactor performance was tested, along with the use of cow manure as an additional substrate to enhance reactor stability. Bench-scale continuously stirred tank reactors were operated at 38 °C with an initial hydraulic retention time of 20 days. Biogas production was recorded daily and compared to a control reactor. To assess reactor stability, pH, alkalinity, chemical oxygen demand (COD) and volatile fatty acid concentration were measured. To manage seasonal production, whey (W) was stored at ambient temperature prior to utilisation. This caused 74 % of the lactose to ferment to mainly L-lactate, accompanied by a pH drop from initially 4.5 to 3.6 and decreased COD. While fresh whey co-digested with primary sludge (PS) did not improve the biogas production, stored whey utilised at the ratio 10:3 (PS:W) improved the biogas production to 150 % of the control. Cow manure (CM) co-digested with primary sludge and fresh whey at the ratio 10:7:1 (PS:W:CM) improved the biogas production by up to 200 % after slow acclimatisation to the whey. The addition of cow manure to primary sludge and stored whey did not improve the biogas production beyond the 150 % achieved without cow manure. Investigation into why cow manure improved biogas production in primary sludge and whey co-digestion established that fungi found in cow manure could play an important role in the hydrolysis of complex material and therefore the biogas production. Improved biogas production from fresh whey was only achieved when cow manure was provided. It appeared that additional lactic acid bacteria supplied by cow manure was required to ferment the high lactose concentration in fresh whey. This work has shown how the seasonal availability of whey can be effectively used to improve the biogas production from municipal sludge digestion. During peak milk production fresh whey could be co-digested with primary sludge and cow manure at the ratio 10:5:1 (PS:W:CM) achieving 178 % biogas production. If cow manure is difficult to obtain, the ratio 10:3:0.1 is recommended, achieving 138 % biogas production. When the availability of fresh whey decreases, stored whey at the ratio 10:3 (PS:W) is recommended without cow manure, producing 150 % biogas compared to primary sludge alone. Utilising whey as a viable substrate would improve productivity of municipal sludge digesters as well as alleviating environmental issues associated with whey disposal.
Keywords: Sewage sludge; Biogas production; Casein whey; Anaerobic bacteria; Cow manure